Micromachined Calibration Chip with Heat Source and Temperature Sensors for Scanning Thermal Metrology (SThM). (2015) - Lemaire, E.; Nguyen, T.P.; Bontempi, A.; Thiery, L.; Teyssieux, D.; Vairac, P.; Shea, H.; Briand, D.
Abstract: The monitoring of heat flux is becoming more and more critical for many technologies approaching nanometric dimensions. Scanning Thermal Microscopy (SThM) is one of the tools available for thermal measurement at the nanoscale. This measurement technics needs calibration samples. Therefore, micro-hotplates made of platinum heater suspended on thin silicon nitride (SiN) membranes were fabricated for the calibration of Scanning Thermal Microscopy probes. The objective is to obtain heated reference samples with localised resistive temperature sensors (RTD) on the membrane to probe the temperature on a micro-scale area (typically 10x10 μm 2 ). This sensing area is dedicated to (1) quantify the thermal resistance between the SThM tip and hot surface contact; and to (2) evaluate the perturbation induced by the probe on the heat dissipation when the contact measurement is performed. In this communication, we report on the thermal design of low-power calibration chip and their fabrication, as well as the electro-thermal characterization of sensitive RTDs made using e-beam technology. Thermal contact measurements using a thermocouple based SThM probe validated the functionality of the calibration chip.